ANALISIS TENTANG CARA BELAJAR EFEKTIF PESERTA DIDIK KELAS VII SMP N 2 SUNGAI RAYA - Nuraisyah, Siti; Astuti, Indri; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe common problem in this research is "How to learn effectively the students of class VII in SMP Negeri 2 Sungai Raya". While general purpose of this research is to know "Effective learners learners class VII SMP Negeri 2 Sungai raya".This research method using descriptive method. Form of research used in this research is survey study. The population in this study amounted to 270, with a sample of 72 students who took 25% of the population with random sampling technique. While data collecting technique used is indirect communication technique. The data collection tool used is an effective learning questionnaire.Based on the results of data analysis of how effective learners learners in class VII SMP Negeri 2 rivers good classified, it can be concluded that, how effective learners learners in class VII SMP Negeri 2 rivers reached 73.37% which is quite good.Â Keywoard: effective learners, descriptive method